2001
DOI: 10.1128/jcm.39.11.4169-4171.2001
|View full text |Cite
|
Sign up to set email alerts
|

Unsatisfactory Performance of Flow Cytometer UF-100 and Urine Strips in Predicting Outcome of Urine Cultures

Abstract: UF-100 flow cytometer and urine strip results were cross-interpreted to predict culture outcomes. The best negative predictive value was obtained with bacteria at >1,000/l, white blood cells at >20/l, or leukocyte esterase positivity. Nine of 24 false negatives were clinically significant. Thus, UF-100 and urine strip results do not accurately predict the outcome of cultures.Urinary tract infection (UTI) is a common cause of human illness, and failure to diagnose and treat it properly can lead to further chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…However, it still had a rather high false-negative rate. The UF-100 was also reported to have a high false-negative rate in the detection of significant bacteriuria (11). In this study, we developed a new flow cytometry-based automated device which was specific for accurate enumeration of bacterial cells in urine and tested the feasibility of the device for detecting significant bacteriuria.…”
Section: Discussionmentioning
confidence: 99%
“…However, it still had a rather high false-negative rate. The UF-100 was also reported to have a high false-negative rate in the detection of significant bacteriuria (11). In this study, we developed a new flow cytometry-based automated device which was specific for accurate enumeration of bacterial cells in urine and tested the feasibility of the device for detecting significant bacteriuria.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of studies that compare the bacterial and leukocyte counts with the UF-100 with urine culture for the diagnosis of UTI vary widely. While some studies have reported an adequate performance in relation to urine culture (6,9,10,13), others have found a relatively large number of false negatives, which decreases sensitivity and makes the UF-100 unsuitable as a screening method to detect negative culture samples (2,15,22). Comparing studies is difficult though, since reported sensitivities and specificities depend on the definition used for gold standard positive and negative urines, and these definitions vary among laboratories.…”
mentioning
confidence: 89%
“…It has already been reported that most FN results are observed primarily in certain patient groups, including those that are immunosuppressed, renal transplant recipients or pregnant woman (2). Of course, it is possible that in some of these cases, microbiologists ''over'' interpret the urine culture and consider them significant.…”
Section: Although the Sysmexmentioning
confidence: 99%
“…᭨ UF-100 detects a large percentage of UTIs, reported sensitivities are only in the range of 70%-90% (1,2,15,18). However, some investigators reported higher sensitivities ()95%), but this caused the specificity to drop to values as low as 15%-49% (11,12).…”
Section: Although the Sysmexmentioning
confidence: 99%
See 1 more Smart Citation